Production of Natural Rubber Grafted Styrene Copolymer Latex as Water Base Coatings - M Utama; K Widjaja (Atom Indonesia, 2006)
Twelve kinds formulation of natural rubber grafted copolymer styrene (NR-g-S) prepared by gamma radiation co-polymerization technique has been carried out. The characteristic of NR-g-S and its water base coating such as molecular structure, particle size, and the properties of latex and its film were evaluated. The results showed that the NR-g-S latex as a water base coating has low viscosity, height strength,  good grease resistance, good flexibility, good aging and corrosion resistance on concrete cement and metal. The average particle size is between 270-300 nm, and the bonding between  poly-isoprene of NRL and styrene molecules were grafted copolymer